PEMBERDAYAAN MASYARAKAT OLEH SARJANA PENGGERAK PEMBANGUNAN PERDESAAN (PSP3) DI KELURAHAN SEKIJANG KECAMATAN BANDAR SEKIJANG KABUPATEN PELALAWAN TAHUN 2014-2015 - Atikah Mayella; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Poverty and employment is a problem that has long faced by people in rural areas. The government continues to accelerate the improvement of the welfare of the rural community with a variety of programs, one of which is the Youth Program Bachelor of Rural Development Activator (PSP3). However, the issue of low participation of government, budget and access to CSR and private CD still faced by PSP3 in community empowerment in the Village District of Bandar Sekijang Sekijang Pelalawan. This study analysis based on the theory of empowerment. This study uses qualitative research. Unit data analysis by means of interviews to several sources, with data on primary and secondary research.The results of this study indicate that; First, community empowerment by PSP3 in the Village District of Bandar Sekijang Sekijang Pelalawan done through facilitating development planning, facilitation of capacity building, knowledge, insight, attitudes and skills of youth, facilitating the development of economic efforts and the facilitation of networking and cooperation among the parties in development. Second, the inhibiting factors of community empowerment by PSP3 Village Sekijang District of Bandar Sekijang Pelalawan grouped into two factors: internal factors which include; lack of facilitators, lack of support and lack of support prasarna budget. While external factors, namely; the lack of participation of government and private sector and the lack of support for other stakeholders.Keywords: Empowerment, PSP3, Public Welfare